Numerical Investigation on Interference of Multiple Hydraulic Fractures in Layered Formation - Li, Zhichao; Wang, Shuren; Li, Lianchong; Zhang, Jiyun (Frontiers in Earth Science, 2022)
Staged treatment in vertical wells is extensively applied in layered formation to obtain commercial exploitation of hydrocarbon resources. Large-sized heterogeneities always exist between multiple hydraulic fractures in different layers. To reveal the interference of multiple hydraulic fractures in layered formation, a series of numerical investigations were conducted based on the cohesive zone finite element method. The results show that the sole stress interference is too small to exert an effective impact on adjacent pay zones, which is quite different from those in horizontal wells. The flow distribution in one pay zone can reach 56.2%, which is more than five times the magnitude of the least 10.5% during the fracturing in three pay zones. The fracture size heterogeneities are mainly caused by the interference of the fluid flow into multiple perforation tunnels in different pay zones. To further clarify how the flow distribution in the pay zones is affected, five related factors, including perforating thickness, pay zone thickness, rock permeability, minimum horizontal stress of the pay zone, and rock strength, are analyzed. The results show that it is through the manner of flow distribution adjustment in each pay zone that the five factors affect the fracture size. This study is of critical importance to clarify how the multiple hydraulic fractures from vertical wells interfere in layered formation and explain why the hydraulic fractures we get in the field are far away from what we want ideally.